Application of Remote Sensing and Geographic Information System in Counter Terrorism in Sub Saharan Africa - Dukiya, J. J. (European Journal of Applied Sciences, 2025)
That Sub-Saharan Africa is threshing floor for human blood is not an overstatement. Terrorism of divers nomenclature is everywhere, and they seem to be operating with impunity under a failed state. This review paper focuses on the capability of remote sensing and GIS in counter terrorism in Sub Saharan Africa with the epicentres at Gulf of Guinea and the Horn of Africa (Somali). To this end, the paper reviewed case studies in use of multi-temporal HSR-5M satellite imagery and ARCGIS that carry out area surveillance of elected area. While SASTRA resource search engine was used to access secondary data on Big Data, remote sensing, and GIS applications in security. The review find out that Big-Data in GIS environment and sensors bearing Unmanned Area Vehicle (UAV), and natural birds are veritable tools for modern enemies’ surveillance and logistic supply for troops. The paper therefore recommended that all the African countries should invest more in the security agencies capacity development, remote sensing and GIS hardware and software for effective territorial security and defence.